Inovasi Program “Sapa Mas Pj” Sebagai Kanal Layanan Pengaduan Pada Dinas Komunikasi Dan Informatika Kota Mojokerto - Ramadhani, Andina Ardana; Arif, Lukman (Innovative: Journal Of Social Science Research, 2025)
Public services are people's rights that must be fulfilled by the government. However, it turns out that there are still obstacles and challenges in implementing public services that have not been managed effectively, resulting in many complaints not being handled. This research aims to determine the extent to which the Sapa Mas Pj program has improved the efficiency, effectiveness, and accessibility of complaint services for the people of Mojokerto City. This research uses a qualitative descriptive research method with data collection techniques through interviews, literature studies based on journals and websites relevant to this research, and the researcher's reports and documentation. Researchers use Rogers' theory of public service innovation with five indicators, namely: relative advantage, coincidence, complexity, the possibility of being tried, and ease of observation. The results of this research show that the implementation of the Sapa Mas Pj complaint channel innovation has gone well as seen from the indicators of relative profitability, desirability, possibility of being tried, and ease of observation. However, there are still obstacles and challenges in complexity indicators.